2018
DOI: 10.1097/aap.0000000000000782
|View full text |Cite
|
Sign up to set email alerts
|

Clotting-Factor Concentrations 5 Days After Discontinuation of Warfarin

Abstract: Based on 40% activity of CFs, patients with INRs of 1.2 or less can be considered to have adequate CFs to undergo neuraxial injections. The number of patients with an INR of 1.3 and 1.4 is too small to make conclusions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…23,24 In contrast, in VKA treated patients, an INR of at least 1.3 may be associated with factor activity levels less than 40% and disturbed coagulation. 5 Recent data from retrospective studies found that an INR range of at least 1.0 to 1.25 after major orthopaedic surgery or 1.0 to 1.49 after major general surgery increased the occurrence of major surgical bleeding. 6,25,26 Similar results were reported after cholecystectomy, 27 wherein the bleeding frequency predominantly increased in the presence of an INR of at least 1.5.…”
Section: Discussionmentioning
confidence: 99%
“…23,24 In contrast, in VKA treated patients, an INR of at least 1.3 may be associated with factor activity levels less than 40% and disturbed coagulation. 5 Recent data from retrospective studies found that an INR range of at least 1.0 to 1.25 after major orthopaedic surgery or 1.0 to 1.49 after major general surgery increased the occurrence of major surgical bleeding. 6,25,26 Similar results were reported after cholecystectomy, 27 wherein the bleeding frequency predominantly increased in the presence of an INR of at least 1.5.…”
Section: Discussionmentioning
confidence: 99%
“…Benzon et al, studied the remaining anticoagulation effect of warfarin five days after its discontinuation. In the majority of patients (n = 21), the international normalized ratio (INR) normalized to less than 1.2, which was considered adequate for safe neuraxial procedures 164 . A small number of patients (n = 2) had INR values of 1.3 or 1.4.…”
Section: - What Is the Optimal Protocol For Management Of Patients Wh...mentioning
confidence: 99%
“…A small number of patients (n = 2) had INR values of 1.3 or 1.4. However, the safety of this INR range for neuraxial injections was considered inconclusive 164 . Narouze et al, and the American Society of Regional Anesthesia (ASRA) published guidelines recommending stopping warfarin five to six days before interventional spine and pain procedures, with a goal INR of 1.4 or less 165 .…”
Section: - What Is the Optimal Protocol For Management Of Patients Wh...mentioning
confidence: 99%
“…6 The ASRA further states that for neuraxial procedures, INR should be 1.4 or less; however, in patients whose warfarin was stopped for 5 to 6 days, the INR should be normalized to <1.2. Benzon et al 7 investigated the effect of warfarin on INR and clotting factors (II, VII, IX, X) 5 days after discontinuation of warfarin. Twenty-one patients were studied, and it was found that if INR < 1.2, the median clotting factor activity was >40% and considered adequate for neuraxial procedures.…”
Section: Warfarinmentioning
confidence: 99%